A photoacoustic pulse-echo probe for monitoring surface stone mechanical properties: Validation tests in consolidation of Carrara marble. (30th October 2018) - Ciofini, Daniele; Mencaglia, Andrea Azelio; Siano, Salvatore
Graphical abstract: Highlights: A photoacoustic probe and method for surface characterization of stones are proposed. The approach allows quantifying surface stone deterioration and consolidation effects. Effectiveness in assessing the properties of consolidation treatments was demonstrated. Abstract: The present work focuses on the development and validation of a laser-based photoacoustic sensor for non-destructive monitoring of surface stone mechanical properties. The sensor is constituted of a carbon black target excited by fiber-coupled Q-Switched Nd:YAG(1064 nm) laser with variable pulse duration between 10 and 50 ns, a superimposed PVDF film transducer, and gel coupler. The high optical absorption of the target and its relatively large lateral size allowed generating planar longitudinal pressure transients of amplitude around 1 MPa using a laser pulse fluence of about 8 mJ/cm 2 . The probe provided an almost flat spectral response over a bandwidth of 7.5–30 MHz. Thanks to the high pulse-to-pulse laser emission stability, the pressure transients were highly reproducible in amplitude and waveform. These features and the FFT analysis of the back reflected signal were exploited to characterize the surface mechanical properties of decayed Carrara marble upon consolidation. Treatment tests were carried out using three commercial products: acrylic-siloxane polymer, a fluoroelastomer-acrylic polymer, and ethyl-silicate. The acoustic reflection and then surface sound speed spectra were measured and analyzed for the first time within a spectral window of 1–30 MHz. Surface speed spectra and dephasing derived from reflectance measurements resulted to be essential parameters for characterizing and monitoring stone consolidation. The results achieved provide evidence that the technique proposed offers significant advantages with respect to traditional approaches and can represent an effective tool in conservation-restoration of stone artifacts, wall paintings, and other.